Implementasi Metode Forward Chaining dan Certainty Factor dalam Mendiagnosis Tanaman Cabai Berbasis Website - Putri Dwi Rahayu; Budi Arif Dermawan; Betha Nurina Sari (Peneliti.net, 2022)
The chili production process can be influenced by several factors ranging from soil fertility, poor seed quality, and the influence of weather. Weather factors in the rainy season can result in high air humidity so that pests and diseases easily develop and spread causing damage or death of chili plants. In the process of handling these problems requires an expert or extension worker in the related field. To overcome these problems, it is necessary to create a system that has the ability to detect chili plant diseases by implementing the knowledge possessed by an expert into applications, namely an expert system. The expert system that will be implemented is an expert system for detecting chili plant diseases using the forward chaining method to perform reasoning, and using the certainty factor method to calculate the level of confidence in the diagnosis results. The system will analyze based on the symptoms experienced by farmers with the aim of helping farmers who still do not understand the attacks that occur on chili plants. The results of the evaluation of the system show that the system is able to run very well, besides the results of processing the questionnaire data distributed to users indicate that the assessment in terms of appearance has a percentage of 75% and the percentage obtained in terms of benefits is 74.37%.